Congenital Tarsal Kink Syndrome: Literature Review and Case Report - Speranța Schmitzer; Sorin-Dorin Haidu; Ioana Claudia Popteanu; Anca Angela Simionescu (MDPI AG, 2022)
Background: The congenital tarsal kink syndrome is a rare form of congenital upper eyelid entropion associated with cardiovascular, musculoskeletal or central nervous system disorders. This syndrome must be recognized and surgically treated as a perinatal emergency to avoid associated complications-corneal ulcer, corneal leucoma, secondary amblyopia and decreased vision among children. Methods: A literature review was conducted to clarify the diagnosis particularities and the corrective surgery options of the congenital entropion on the upper eyelid. Results: Four relevant studies were found by researching the Web of Science and PubMed databases up to November 2021 for "congenital tarsal kink syndrome" and "congenital upper eyelid entropion". Conclusions: In this paper, we present a case of congenital unilateral entropion of the upper left eyelid in the context of a tarsal kink syndrome in a one-month old infant, manifested by the absence of eyelashes on the upper eyelid of the left eye, hyperlacrimation and conjunctival hyperemia. Essential in managing the upper eyelid entropion is protecting the cornea. Furthermore, correcting a tarsal kink is eminently surgical, choosing between open or closed procedures. Herein, we address the difficulty in the timely diagnosis of this uncommon condition and make formal recommendations based on all reported cases.